DENTAL TRAUMATIC AVULSIONS: AN ANALYSIS OF THE PERFORMANCE AND MAINTENANCE OF REPLANTED TEETH IN THE FIRST-YEAR POST-INJURY - Marinho Barcellos, Bhárbara (2025)
Aim: This study aims to examine the factors influencing the decision to perform replantation following avulsion of permanent teeth, as well as factors affecting the maintenance of replanted teeth in the first-year post-injury. Material and Methods: This retrospective analysis involved examining dental records and periapical radiographs of patients with avulsed permanent teeth. Demographic information, details regarding traumatic lesions, and treatment specifications were extracted from dental records. Radiographs obtained during the initial appointment were used to assess root maturity, and the ones at the one-year follow-up examination evaluated the maintenance of replanted teeth, along with the presence of endodontic therapy, bone loss, periapical lesions, and inflammatory or replacement resorption. Chi-square tests and hierarchical Logistic Regression Analysis were employed to identify factors associated with replantation success and maintenance of replanted teeth after one year. Results: Data from 106 patients and 154 avulsions were collected according to predefined criteria. Of the 154 teeth, 102 (76.2%) underwent replantation. Patients over 13 years of age at the moment of the traumatic injury, those with avulsion of more than one tooth, and those with associated alveolar bone fractures were less likely to undergo replantation. In the first-year post-injury, 71 of the 102 replanted teeth (70.3%) were retained. Tooth loss within the first-year follow-up was more likely in male patients, individuals over 13 years old at the moment of the avulsion, and those with associated alveolar bone fractures. Conclusions: Patient age and alveolar bone fractures during traumatic injuries were identified as factors associated with both replantation outcomes. Patient gender influenced the presence of the tooth in the first-year postinjury, while avulsion of more than one tooth showed an association with replantation performance.